Vanity in Politics: A Problem? - Guido Suurmond; Otto H. Swank; Bauke Visser (Tinbergen Institute, 2002)
Can vanity do any good? It may seem obvious to answer this question in the negative, as economists have shown how reputational concerns lead agents e.g. to ignore valuable information, to herd, and to become overly risk averse. We explore how proud agents may be a social blessing. An agent may exert effort to become informed about the uncertain benefits of aproject. A smart agent's efforts make him better informed; a dumb agent's efforts are to no avail. If an agent does not know his type, pride is socially beneficial. If an agent knows his type, a dumb agent takes inefficient, unconventional decisions to mimick a smart agent. The latter exerts more effort in order not to be mistaken for a dumb. This holds whether or not project rejection is a save haven for the dumb.
Keywords: D72; D83; D84; 330; Reputation; Information Collection; Reputation; Asymmetrische Information; Neue politische Ökonomie; Theorie